Fraud Detection through Internal Control Systems, Organizational Culture and Ethical Behavior - Tiara Rani Santoso; Dwi Hayu Estrini; Ayu Sarah Sulistyawati; Agnes Ivena Engracia (E-Jurnal Akuntansi, 2025)
Testing the tendency to commit fraud can be seen from several factors, namely the internal control system, organizational culture and ethical behavior as well as testing the role of accounting information systems in ethical behavior against fraud. Primary data was collected through a survey of 146 respondents given to employees of the Semarang Commissariat Bank Perkreditan Rakyat. Data analysis uses multiple regression path analysis using WarpPLS software. The research results reveal that internal control, organizational culture and ethical behavior have a significant negative effect on the tendency to commit fraud. These results indicate that there is a partial mediation effect on the ethical behavior variable. However, the effectiveness of the accounting information system does not have a moderating effect on ethical behavior on the tendency to commit fraud. This is due to pressure, opportunity and rationalization from employees themselves which can influence the tendency to commit fraud.